PENGUATAN KAPASITAS SDM APARATUR DESA MELALUI MANAJEMEN PELAYANAN PUBLIK DAN KINERJA DI PAUH, KOTA PADANG - Yulihardi, Yulihardi; Febriani, Rina; Suhanda, Mya Yuwanita; Suandi, Edi; Afrida, Afrida (Komunitas Manajemen Kompetitif, 2024)
Improving the quality of public services at the village level is a crucial prerequisite for realizing effective, accountable, and community-satisfaction-oriented governance. However, the human resource capacity of village officials, particularly in public service management and performance, remains a major obstacle. This issue was also identified in the Pauh area of ​​Padang City, where village officials face limited understanding of service standards, performance management, and a professional and responsive work culture. This community service program aims to strengthen the capacity of village officials through training and mentoring in public service management and performance. Activities are implemented using a participatory and needs-based approach, including problem identification, thematic training, case study discussions, service simulations, and mentoring in the implementation of service standards and performance evaluation. The materials covered the concept of public service, principles of good governance, performance management, the development of service standards, and indicator-based evaluation. Targeted outputs include improving the competency of village officials, the development of training modules, performance improvement models, scientific articles, and policy recommendations. In the long term, this program is expected to drive improvements in the quality of public services and strengthen professional and sustainable village governance in Pauh, Padang City